Ion-kinetic modeling of Mercury’s magnetosphere: a reference for BepiColombo’s sixth flyby - Daniel Teubenbacher; Yasuhito Narita; Ali Varsani; Daniel Schmid; Gunter Laky; Willi Exner (Earth, Planets and Space)
Abstract The BepiColombo mission offers a unique opportunity to investigate Mercury’s magnetosphere and its interaction with the solar wind. This study presents a model-based reference for ion and magnetic field observations during the sixth Mercury flyby (MSB6) on January 8, 2025, using the global 3D hybrid plasma code AIKEF. Simulations include 12 solar wind and IMF conditions, incorporating a kinetic treatment of ions and a self-consistent sodium exosphere. Differential ion energy spectra are computed along the high-latitude MSB6 trajectory for both solar wind-originated protons and exospheric sodium ions. Five distinct plasma regions are identified, including a southern plasma mantle as the transition region from magnetosheath plasma to lobe plasma; a southern lobe region characterized by $$E × B$$ E × B convection; the central tail current sheet with a fast planetward plasma flow due to magnetic reconnection; a northern mantle or cusp-like region containing escaping sodium ions; and a faint pick-up population upstream of the bow shock. Ion energies reach up to 10 keV for protons and 30 keV for sodium under strong solar wind conditions. Notably, the high-latitude plasma mantle exhibits a clear energy dispersion-like feature, with its structure sensitive to solar wind dynamic pressure. Stronger solar wind input leads to steeper ion energy gradients in the spectra, while weaker conditions result in broader mantle structures ranging from 400 to 2000 km (3–26 local proton gyroradii). Cross-magnetospheric electric potentials of $$φ _{\text{tail}} = 14{-}32\,\text{kV}$$ ϕ tail = 14 - 32 kV align with observational estimates. These findings provide critical insights into Mercury’s magnetospheric dynamics and form a foundation for interpreting BepiColombo’s observations. Graphical Abstract